2023
DOI: 10.1038/s41419-023-06023-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SphK1/2 by SKI-178 inhibits prostate cancer cell growth

Lu Jin,
Jin Zhu,
Linya Yao
et al.

Abstract: Sphingosine kinases (SphK), including SphK1 and SphK2, are important enzymes promoting progression of prostate cancer. SKI-178 is a novel and highly potent SphK1/2 dual inhibitor. We here tested the potential anti-prostate cancer cell activity of SKI-178. Bioinformatics analyses and results from local tissues demonstrated that that both SphK1 and SphK2 are upregulated in human prostate cancer tissues. Ectopic overexpression of SphK1 and SphK2, by lentiviral constructs, promoted primary prostate cancer cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…The migration and invasion of tumor cells are the key links in the metastasis process [27]. SPHK1 has demonstrated tumor cell migration and invasion functions in breast cancer [28] and prostate cancer [29]. Consistent with the above ndings, our data showed that SPHK1 knockdown inhibited GC cell migration and invasion, while overexpression of SPHK1 did the opposite (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The migration and invasion of tumor cells are the key links in the metastasis process [27]. SPHK1 has demonstrated tumor cell migration and invasion functions in breast cancer [28] and prostate cancer [29]. Consistent with the above ndings, our data showed that SPHK1 knockdown inhibited GC cell migration and invasion, while overexpression of SPHK1 did the opposite (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, ceramide generation via de novo synthesis and sphingomyelin hydrolysis aids in treating cancer. On the other hand, the suppression of enzymes that deplete ceramide-for instance, ceramidases, glucosylceramide synthase, or SphKs-when combined with standard cancer therapies that dysregulate these enzymes, reveal promising improvements in the patient response to various cancer therapies [38][39][40].…”
Section: Sphingolipid Metabolismmentioning
confidence: 99%